Comparative Study on Wildlife Impact in Electric Fenced and Unfenced Communities in Dungmin Geog, Pemagatshel, Bhutan - Chedup, Sangay; Dendup, Tashi; Dorji, Ugyen; Tshering, Cheten; Maya Tamang, Santa (International Journal of Environment, 2023)
Human wildlife conflicts are one of the major challenges for wildlife conservation throughout the globe, and electric fencing (EF) has been used as one of the means to address those challenges. However, the comprehensive study to assess its effectiveness is lacking in many parts. Thus, this study attempted to understand the impact on crops and crop guarding time before and after fencing in communities having both fenced and unfenced households in three Chiwogs under Pemagatshel district. The data were collected through total enumeration using semi-structured interviews from 80 households. Wilcoxon’s signed-rank test showed that the electric fence (EF) has a significant difference (p=0.00, M=50) to farmers in reducing their common crop loss to wildlife and protected staple crop damages (maize). However, bitter buckwheat and radish continued attacking by barking deer. EF reduced both day and night guarding time significantly to all common crops. On the contrary, the unfenced farmers have suffered from increasing pressure from the wildlife after the establishment of EF in their community. Maize and potato damage have significantly increased after EF. There was a significant difference in maize and potato’s day and night guarding time before and after EF. Only night guarding time has a significant difference between sweet buckwheat and bitter buckwheat before EF and after EF. Therefore, it emphasizes the need to cover the whole community by EF promoting crop production and reducing crop guarding against wildlife to avert similar issues in other communities.